The Correlation Among The Attitudes Toward Learning English And Achievements of The First Year Students of Air Transportation Management II In CASEA Surabaya - Fatmawati Fatmawati (Jurnal Penelitian)
This study attempts to know the correlation among the attitudes toward learning English, and achievements of the first year Air Transportation Management II students of Casea Surabaya. This study is limited in Academic year 2015/2016. The limitation based on the following consideration; the first, in Academic year 2015/2016 is the moment of the students to measure their skills during one year; the second, they still have the time to improve their English skill and study hard than before.Based on the research problems, research objectives and explanations that have been given, the writer can deliver the conclusion as follows; The mean of the attitudes questionnaire is 63.26. It is a good category and there is significant correlation between the students' English achievement and the students' achievement in the first year of CASEA Surabaya. From the interpretation of data, the score is-0,13. Consider of the table significant level is including a low correlation